Do Thirty-Second Post-activation Potentiation Exercises Improve the 50-m Freestyle Sprint Performance in Adolescent Swimmers? - Abbes, Zied; Chamari, Karim; Mujika, Iñigo; Tabben, Montassar; Bibi, Khalid W.; Hussein, Ali Mostafa; Martin, Cyril; Haddad, Monoem (Frontiers in Physiology, 2018)
Objectives This study aimed to investigate the performance and biomechanical, physiological and psychophysiological effects of a simple and easily organized post-activation potentiation (PAP) re-warm-up performed before a 50-m freestyle swimming dash. Methods Regional level male adolescent swimmers performed four experimental trials on different days. The control trial involved a standard 1200-m warm-up followed by 30 min of rest and a maximal 50-m freestyle swim sprint. The PAP trial involved the same protocol; however, the PAP loading protocol was completed after a 20-min rest (10 min pre 50 m). The different PAP loading protocols involved the subjects in completing a 30-s maximal effort of push-ups (PU - upper body), squats (SQ - lower body) and burpees (BP - lower & upper body). The performance (time-trial), biomechanical (stroke length, stroke frequency, stroke index), physiological (blood lactate concentrations, heart rate), and psychophysiological (perceived effort) variables were assessed during all trials. Results The main results showed that the 30-s PAP loads used in this investigation 10 min before the 50-m race had no effect on swimming performance. Before the 50-m race, the lactate values were significantly higher after the PU and BP PAP loads compared to the control condition (p<0.05). At three minutes after the 50-m sprint, significant differences were found between the control condition and the PU and SQ PAP loads (P(CC-PU)=0.018; P(CC-SQ)=0.008, respectively). The mean HR values in response to the different conditions illustrated no significance of interaction between the conditions (P > 0.05). The timing of the post-warm-up could be unsuitable, even though it fits within the range of the 4 to 12 min cited by several studies as being sufficient to enhance performance. Conclusions The present study PAP protocol of the present study did not allow the identification of the factors that potentially resulted in the lack of any alteration in 50-m swim sprint improvement: 10-min lapse between the PAP exercise and performance and/or the load/intensity of the PAP. Further studies are warranted to investigate ways to improve swimming performance with simple body mass exercises performed in-between the end of pool warm-up and swimming performance.